S-, P-, and D-wave resonances in positronium-lithium-atom scattering - Biswas, P. K. [UNESP] (American Physical Society (APS), 2000)
We investigate ortho-positronium-lithium-atom (Ps-Li) scattering using static-exchange and three-Ps-state coupled-channel calculations. The present three-PS-state scheme, while closely agreeing with the resonance and binding energies in the Ps-H system, predicts S-, P-, and D-wave resonances at 4.25 eV, 4.9 eV, and, 5.25 eV. respectively, in the electronic spin-singlet channel of Ps-Li scattering. The present calculation also yields a Ps-Li binding in this attractive singlet channel with an approximate binding energy of 0.218 eV, which is in adherence with the recent findings of a chemically stable PsLi system using stocastic variational and quantum Monte Carlo calculations. We further report elastic, Ps(2s)-, and Ps(2p)-excitation cross sections at low to medium energies (0.068-30 eV).